Malrotated Gut Mimcking Gastric Out Let Obstruction in an Adolescent- A Case Report - Siddique, MAB; Hannan, ABMA; Haque, MM; Alam, I (TAJ: Journal of Teachers Association, 2009)
Most of the patients with mal-rotated gut present in neonate and infancy either with acute strangulating obstruction or with recurrent episodes of sub-acute obstruction. Here an adolescent male patient of 17 years with mal-rotated gut presented with upper abdominal pain, vomiting after meal and loss of weight mimicking gastric out let obstruction. Because of rarity of the condition at this age, we are inspired to report this case. doi: 10.3329/taj.v18i1.3307 TAJ 2005; 18(1): 53-54